Metallic iron in cornflakes. Issue 4 (25th March 2020) - Lermyte, Frederik; Zhang, Wen-Ying; Brooks, Jake; Huband, Steven; Collingwood, Joanna F.; Lees, Martin R.; Rayman, Margaret P.; Sadler, Peter J.
Abstract : Magnetometry and X-ray analysis show that the iron in cornflake-style cereals fortified with this essential element at levels up to 14 mg per 100 g, is micron-sized body-centred cubic metallic iron, partially soluble at stomach pH. Abstract : Iron is an essential element, and cornflake-style cereals are typically fortified with iron to a level up to 14 mg iron per 100 g. Even single cornflakes exhibit magnetic behaviour. We extracted iron microparticles from samples of two own-brand supermarket cornflakes using a strong permanent magnet. Synchrotron iron K-edge X-ray absorption near-edge spectroscopic data were consistent with identification as metallic iron, and X-ray diffraction studies provided unequivocal identification of the extracted iron as body-centred cubic (BCC) α-iron. Magnetometry measurements were also consistent with ca. 14 mg per 100 g BCC iron. These findings emphasise that attention must be paid to the speciation of trace elements, in relation to their bioavailability. To mimic conditions in the stomach, we suspended the iron extract in dilute HCl (pH 1.0–2.0) at 310 K (body temperature) and found by ICP-MS that over a period of 5 hours, up to 13% of the iron dissolved. This implies that despite its metallic form in the cornflakes, the iron is potentially bioavailable for oxidation and absorption into the body.